1993
DOI: 10.3109/00016489309135847
|View full text |Cite
|
Sign up to set email alerts
|

Stepping Analysis in Patients with Spinocerebellar Degeneration and Parkinson's Disease

Abstract: POLGON (Polarized light goniometer) was used to evaluate ataxia during stepping movements in patients with spinocerebellar degeneration (SCD) and Parkinson's disease. The measurements included mean angular change of shoulders (M.A.C.S.) and its coefficient of variation (C.V.). In patients with SCD, the values of M.A.C.S. were significantly larger at 1.0 step/s than those at other stepping rhythms. This results suggests that the stepping rhythm of 1.0 step/s is useful for the detection of cerebellar ataxia. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Virtual teacher's reference movements were presented as a stepping-inplace (SIP) task. SIP test has been applied in various clinical and rehabilitative applications [10][11][12]. A preliminary investigation [15] showed that healthy subjects can adapt to the virtual teacher very quickly.…”
Section: Introductionmentioning
confidence: 99%
“…Virtual teacher's reference movements were presented as a stepping-inplace (SIP) task. SIP test has been applied in various clinical and rehabilitative applications [10][11][12]. A preliminary investigation [15] showed that healthy subjects can adapt to the virtual teacher very quickly.…”
Section: Introductionmentioning
confidence: 99%
“…During the last decade, the test has also entered the rehabilitation environment. The SIP test has been applied to stroke patients [3], patients with Parkinson disease [4], and amputees. These previous studies have focused either on evaluating the test as an indicator of a disease, or on assessing patients' strategies for overcoming limited movement in their lower extremities.…”
Section: Introductionmentioning
confidence: 99%